Investigation on the Hydrate Blockage Avoidance Performance of Two Anti-Agglomerants and Their Mixture with PVP - Sunan Wang; Litao Chen; Lei Guo; Jiansheng Luo; Liangliang Ren; Xiong Xiang; Tie Geng; Changhong Yu; Zilong Meng (Molecules)
The hydrate blockage avoidance performance of two anti-agglomerants (coconut amidopropyl dimethylamine, propylene bis (octadecylamidopropyl dimethylammonium chloride)) and their mixtures with polyvinylpyrrolidone (PVP) was tested in a high-pressure rocking cell apparatus. The effect of gas–liquid ratio, water content and PVP concentration were analyzed. A method for evaluating the kinetic inhibiting and anti-agglomerating performance of hydrate inhibitors was established. It was found that coconut amidopropyl dimethylamine had good anti-agglomerating performance at a low gas–liquid ratio (0.5) and various water content levels (20~80%), while propylene bis (octadecylamidopropyl dimethylammonium chloride) had a good anti-agglomerating performance only at a low gas–liquid ratio (0.5) and high water content (80%), and the hydrate volume fraction was up to 23.27% for good anti-agglomeration. When PVP was mixed with the above two anti-agglomerants, it was found that coconut amidopropyl dimethylamine could significantly reduce the kinetic inhibition performance of PVP, while propylene bis (octadecylamidopropyl dimethylammonium chloride) had no significant effect on the kinetic inhibition performance of PVP. The maximum subcooling was 4.4 °C. PVP had no significant effect on the anti-agglomerating performance of the two anti-agglomerants, and the maximum hydrate volume fraction was 18.87% when the agglomeration was well inhibited.